2022
DOI: 10.1126/scitranslmed.abo5795
|View full text |Cite
|
Sign up to set email alerts
|

A persistent neutrophil-associated immune signature characterizes post–COVID-19 pulmonary sequelae

Abstract: Interstitial lung disease and associated fibrosis occur in a proportion of individuals who have recovered from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection through unknown mechanisms. We studied individuals with severe coronavirus disease 2019 (COVID-19) after recovery from acute illness. Individuals with evidence of interstitial lung changes at 3 to 6 months after recovery had an up-regulated neutrophil-associated immune signature including increased chemokines, proteases, and marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 78 publications
1
60
0
Order By: Relevance
“…Taken together, these findings support the involvement of multiple inflammatory signals in the expression of KLF2 in LFs during an aberrant immunofibrotic response in severe COVID-19. Indeed, recent data demonstrated an association of inflammatory responses and persistent NETosis with fibrotic processes and impaired lung function in patients that had been severely affected by SARS-CoV-2 [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings support the involvement of multiple inflammatory signals in the expression of KLF2 in LFs during an aberrant immunofibrotic response in severe COVID-19. Indeed, recent data demonstrated an association of inflammatory responses and persistent NETosis with fibrotic processes and impaired lung function in patients that had been severely affected by SARS-CoV-2 [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed that mature neutrophils, but not T cell or B cell subsets, were strongly inversely correlated with recovery pseudotime, suggesting that severe COVID-19 patients who have persistent elevation in mature neutrophil levels over time is predictive for unfavorable disease outcomes. In line with this finding, George et al., 2022 observed increases in systemic neutrophil counts and MPO expression, primarily in severe COVID-19 survivors diagnosed interstitial lung disease in comparison with resolved individuals ( 30 ). Furthermore, MPO levels were positively correlated with disease extent visualized by CT scan and negatively associated with TLCO%.…”
Section: Discussionmentioning
confidence: 83%
“…Culture and infection of pBEC and alveolar epithelial cultures at air-liquid interface (ALI) was performed as previously described 24,25 . Briefly, prior to infection, cells were washed once with PBS and inoculated with equal number of virus particles for Delta, Omicron BA.2 and BA.5.…”
Section: Methodsmentioning
confidence: 99%